On the iteration of quasimeromorphic mappings - Warren, Luke (2020)
This thesis is concerned with the iterative behaviour of quasimeromorphic mappings of transcendental type, which form higher-dimensional analogues of transcendental meromorphic functions on the complex plane. We extend classical Julia theory and results on escaping points from complex dynamics to the new setting. This complements recent dynamical advancements for quasiregular mappings, which are higher-dimensional analogues of holomorphic functions on the complex plane.